2003
DOI: 10.1074/jbc.m300227200
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Is Degraded by Both Autophagy and the Proteasome

Abstract: Parkinson's disease (PD) is characterized by the loss of dopaminergic neurons in the substantia nigra and the formation of aggregates (Lewy bodies) in neurons. ␣-Synuclein is the major protein in Lewy bodies and rare mutations in ␣-synuclein cause early-onset PD. Consequently, ␣-synuclein is implicated in the pathogenesis of PD. Here, we have investigated the degradation pathways of ␣-synuclein, using a stable inducible PC12 cell model, where the expression of exogenous human wild-type, A30P, or A53T ␣-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,094
2
19

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,343 publications
(1,159 citation statements)
references
References 38 publications
44
1,094
2
19
Order By: Relevance
“…We and others have previously demonstrated that a-synuclein aggregates were degraded via the autophagic-lysosomal degradation pathway. 12,13 Furthermore, it has been reported that the autophagy pathway generally plays a major role in clearance of cytoplasmic protein aggregates. 14 Therefore, we examined the effects of PLD1 inhibition on the cytoplasmic accumulation of a-synuclein.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously demonstrated that a-synuclein aggregates were degraded via the autophagic-lysosomal degradation pathway. 12,13 Furthermore, it has been reported that the autophagy pathway generally plays a major role in clearance of cytoplasmic protein aggregates. 14 Therefore, we examined the effects of PLD1 inhibition on the cytoplasmic accumulation of a-synuclein.…”
Section: Resultsmentioning
confidence: 99%
“…α-Synuclein is one substrate and mutant forms of this protein appear to poison both the UPS and autophagy causing Parkinson's disease. [68][69][70] Another shared substrate is inhibitor kappa B alpha (IĸBα), the inhibitor of the transcription factor nuclear factor kappa B. 71 IĸBα appears to be degraded by the UPS and autophagy in different cellular compartments with different rates.…”
Section: Discussionmentioning
confidence: 99%
“…167 Autophagy has been described for intracellular protein aggregates such as polyQ-huntingtin and ␣-synuclein aggregates, and also for tau. 168,169 Rapamycin inhibits mTOR (mammalian target of rapamycin), thereby promoting autophagy. In a Drosophila fruit fly model expressing wild-type or R406W mutant tau, treatment with rapamycin induced autophagic tau degradation and diminished tau-induced toxicity.…”
Section: Tau Clearancementioning
confidence: 99%